Increased pulse pressure is associated with left atrial enlargement in resistant hypertensive patients. (February 2013) - Armario, Pedro; Oliveras, Anna; Hernández-Del-Rey, Raquel; Suárez, Carmen; Martell, Nieves; Ruilope, Luis M.; Sierra, Alejandro De La
Abstract Resistant hypertension (RH) is frequently associated with a high prevalence of target organ damage, which impairs the prognosis of these patients. Considering cardiac alterations in RH, most attention has been devoted to left ventricular hypertrophy (LVH), but data concerning left atrial enlargement (LAE) is less known. This cross-sectional study assessed the factors associated with LAE, with special focus on blood pressure (BP) estimates obtained by ambulatory blood pressure monitoring (ABPM), in 250 patients with RH, aged 64 ± 11 years. LAE and LVH were observed in 10.0% (95% CI 6.3–13.7) and 57.1% (95% CI 50.8–63.5) of patients, respectively. Compared with patients with normal atrium size, those exhibiting LAE were older, more frequently women, had elevated pulse pressure (PP) measured both at the office and by ABPM, and showed higher prevalence of LVH (83% vs 54%; p = 0.016). In a logistic regression analysis, adjusting for age, gender, body mass index, left ventricular mass index and BP pressure estimates, night-time PP was independently associated with LAE (OR for 5 mmHg = 1.28, 95% CI 1.24–1.32; p = 0.001). In conclusion, besides classical determinants of LAE, such as age and LVH, an elevated night-time PP was independently associated with LAE in patients with RH.